The German Aortic Valve Registry (GARY): A Nationwide Registry for Patients Undergoing Invasive Therapy for Severe Aortic Valve Stenosis - Beckmann, A.; Hamm, C.; Figulla, H. R.; Cremer, J.; Kuck, K. H.; Lange, R.; Zahn, R.; Sack, S.; Schuler, G. C.; Walther, T.; Beyersdorf, F.; Böhm, M.; Heusch, G.; Funkat, A. K.; Meinertz, T.; Neumann, T.; Papoutsis, K.; Schneider, S.; Welz, A.; Mohr, F. W.; null (The Thoracic and Cardiovascular Surgeon, 2012)
Background The increasing prevalence of severe aortic valve defects correlates with the increase of life expectancy. For decades, surgical aortic valve replacement (AVR), under the use of extracorporeal circulation, has been the gold standard for treatment of severe aortic valve diseases. In Germany ~12,000 patients receive isolated aortic valve surgery per year. For some time, percutaneous balloon valvuloplasty has been used as a palliative therapeutic option for very few patients. Currently, alternatives for the established surgical procedures such as transcatheter aortic valve implantation (TAVI) have become available, but there are only limited data from randomized studies or low-volume registries concerning long-time outcome. In Germany, the implementation of this new technology into hospital care increased rapidly in the past few years. Therefore, the German Aortic Valve Registry (GARY) was founded in July 2010 including all available therapeutic options and providing data from a large quantity of patients.Methods The GARY is assembled as a complete survey for all invasive therapies in patients with relevant aortic valve diseases. It evaluates the new therapeutic options and compares them to surgical AVR. The model for data acquisition is based on three data sources: source I, the mandatory German database for external performance measurement; source II, a specific registry dataset; and source III, a follow-up data sheet (generated by phone interview). Various procedures will be compared concerning observed complications, mortality, and quality of life up to 5 years after the initial procedure. Furthermore, the registry will enable a compilation of evidence-based indication criteria and, in addition, also a comparison of all approved operative procedures, such as Ross or David procedures, and the use of different mechanical or biological aortic valve prostheses.Results Since the launch of data acquisition in July 2010, almost all institutions performing aortic valve procedures in Germany joined the registry. By now, 91 sites which perform TAVI in Germany participate and more than 15,000 datasets are already in the registry.Conclusion The implementation of new or innovative medical therapies needs supervision under the conditions of a well-structured scientific project. Up to now relevant data for implementation of TAVI and long-term results are missing. In contrast to randomized controlled trials, GARY is a prospective, controlled, 5-year observational multicenter registry, and a real world investigation with only one exclusion criterion, the absence of patients' written consent.
Keywords: aortic valve disease; registry; aortic valve replacement; transcatheter aortic valve implantation; database; outcome; quality of life